Severe acute respiratory coronavirus virus 2 (SARS-CoV-2) infections occurring in healthcare workers after booster vaccination: A comparison of delta versus omicron variants - Kimberly D. Reeves; Christopher M. Polk; Laura A. Cox; Robert T. Fairman; Gregory A. Hawkins; Catherine L. Passaretti; Mindy M. Sampson (Cambridge University Press, 2022)
In this study, we used genomic sequencing to identify variants of severe acute respiratory coronavirus virus 2 (SARS-CoV-2) in healthcare workers with coronavirus disease 2019 (COVID-19) after receiving a booster vaccination. We compared symptoms, comorbidities, exposure risks, and vaccine history between the variants. Postbooster COVID-19 cases increased as the SARS-CoV-2 omicron variant predominated.